2010
DOI: 10.1007/s00277-010-0968-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of idiopathic thrombotic thrombocytopenic purpura treated with rituximab

Abstract: Rituximab may be used to treat patients with thrombotic thrombocytopenic purpura (TTP) refractory to plasma exchange or recurrent disease. While initial response rates are reported to be high, long-term follow-up data of patients treated with rituximab are not available to date however important to estimate the safety and benefit of this treatment. 12 patients with non-familial idiopathic TTP refractory to plasma exchange or with recurrent disease treated with rituximab between 2000 and 2008 were re-examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 26 publications
4
36
0
2
Order By: Relevance
“…An observational study that compared 21 patients with refractory TTP treated with rituximab and 53 historical controls treated with conventional therapy reported that all the patients treated with rituximab experienced platelet count recovery within 35 days compared to only 78% of the control patients (46). The results from 5 other similar studies showed that 83-100% rituximabtreated patients achieved complete remission (47)(48)(49)(50)(51)(52). The relapse rates after rituximab treatment ranged from 0% with a median follow-up of 10 months (47) to 33% with a median follow-up of 73 months (52).…”
Section: Differential Diagnosis Of Ttpsupporting
confidence: 57%
“…An observational study that compared 21 patients with refractory TTP treated with rituximab and 53 historical controls treated with conventional therapy reported that all the patients treated with rituximab experienced platelet count recovery within 35 days compared to only 78% of the control patients (46). The results from 5 other similar studies showed that 83-100% rituximabtreated patients achieved complete remission (47)(48)(49)(50)(51)(52). The relapse rates after rituximab treatment ranged from 0% with a median follow-up of 10 months (47) to 33% with a median follow-up of 73 months (52).…”
Section: Differential Diagnosis Of Ttpsupporting
confidence: 57%
“…However, ADAMTS13 recovery after preemptive rituximab administration was not sustained in up to 30% of patients, 14 and 1 or multiple additional severe drops of ADAMTS13 activity were observed in such patients, typically 18 to 24 months after rituximab administration, as a consequence of peripheral B-cell reconstitution. 24 Interestingly, these patients responded to further rituximab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…8 Consequently, it is important to determine whether preemptive treatment (ie, after remission) with rituximab to deplete anti-ADAMTS13 antibodies could prevent long-term relapses. The encouraging results provided by preliminary studies [9][10][11][12][13][14][15][16][17][18] and the recommendations issued by our group led to the approval in France of rituximab for compassionate use in patients with acquired TTP and persistent severe ADAMTS13 deficiency. To ensure that all patients who received rituximab for TTP would be treated optimally and that their data would be collected in a standardized manner, our group developed recommendations for rituximab administration and for monitoring the biological response to the treatment.…”
Section: Introductionmentioning
confidence: 91%
“…[34][35][36][37] Most of the data are based on case reports and case series where rituximab was used concomitantly with other immunosuppressive agents. 23,34,[36][37][38][39][40][41][42] A recent thoughtful review on this topic adds some clarity to its use in this clinical situation. 43 In several case series, treatment of acute refractory and/or relapsing TTP with rituximab alone resulted in clinical remission in 87% to 100% of patients, and platelet recovery within a median of 11 to 14 days after the first dose.…”
mentioning
confidence: 99%